Opini "Holiday In Hell" dan Keterkaitannya dengan Pemusatan Pembangunan Daerah Pariwisata di Bali - Hasnul, Gyta (Jurnal Bahasa & Pariwisata, 2011)
Bali has been well known as the jewel of the tourism in Indonesia, and its beautyfulness can enchanted all the tourists who visited it. Despite the tragic incident of terrorist bombing in 2002 and 2004, Bali still become one of the most visited place by the tourists from all over the world. However one article from TIME magazine, has been delivering quite a heavy blow for Bali tourism. The article stated that having a holiday in Bali is just like having a holiday in Hell. Eventhough its only due to the garbage waste in the Kuta beach, this article is refering to all tourist destination in Bali as a whole. Some major action should be implied by the local government and its people so the pride of Bali tourism can be saved.